Unusual motor and non-motor symptoms and signs in the early stage of Parkinson’s disease - Teive, Hélio A. G.; Bertucci, Délcio C., Filho; Munhoz, Renato P. (Arquivos de Neuro-Psiquiatria, 2016)
Objective Patients with Parkinson’s disease (PD) may present with unusual motor and non-motor symptoms and signs in the early stage of the disease.Methods Cases were collected over a five-year period at two tertiary movement disorders clinics. All had a diagnosis of PD with unusual presentations defined retrospectively as the presence of complaints not objectively related to any of the classic cardinal signs of parkinsonism or the typical early non-motor features of PD.Results A total of 15 early PD patients fulfilled the proposed criteria, presenting with symptoms such as atypical tremors, shoulder pain, signs related to the rigid akinetic syndrome, as well as cases of asthenia, rhinorrhea, parosmia, dysgeusia, nocturnal sialorrhea, and color discrimination disorders.Conclusions Unusual motor and non-motor symptoms and signs in the early stage of PD can be difficult to interpret. Specialists should be aware of these conditions as clues to a potential diagnosis.
Keywords: Parkinson disease; signs and symptoms